2019
DOI: 10.17687/jeb.0701.02
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Mediating Effect of Organizational Climate in the Context of Malaysian Banking Industry

Abstract: This study examined the mediating effect of organizational climate on the relationship between emotional intelligence and leader-member exchange on organizational citizenship behavior within the context of Malaysian banking industry. The study began by assessing the links that exist between emotional intelligence, leader-member exchange, and organizational citizenship behavior in terms of conceptual theory, context and measurement. The context selected for this study refers to the commercial banking industry o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The hypotheses H1 and H2 are directed towards a mediating role of the learning climate in the relationship between the quality of LMX and employee motivation. Moreover, this supposition is supported by a previous study carried out in Malaysian banking industry, which revealed that organizational climate mediated the relationships between leader-member exchange and employee citizenship behaviors (Vasudevan, and Mahadi, 2019). Therefore, the following hypothesis was proposed: H3: The learning climate will mediate the relationships between the quality of LMX and motivation of public administration employees.…”
Section: Learning Climatementioning
confidence: 67%
“…The hypotheses H1 and H2 are directed towards a mediating role of the learning climate in the relationship between the quality of LMX and employee motivation. Moreover, this supposition is supported by a previous study carried out in Malaysian banking industry, which revealed that organizational climate mediated the relationships between leader-member exchange and employee citizenship behaviors (Vasudevan, and Mahadi, 2019). Therefore, the following hypothesis was proposed: H3: The learning climate will mediate the relationships between the quality of LMX and motivation of public administration employees.…”
Section: Learning Climatementioning
confidence: 67%
“…Finally, it is important to acknowledge and value the emotional and social intelligence of employees. Many private organisations, including banks, have been able to recognise that emotional and social intelligence might boost job productivity as a result of the advantages afforded by these skills (Vasudevan, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, it is evident that the service sector in Malaysia is a place for employment with inflexible time constraints and intense workloads. According to some, such employees struggle to manage and demonstrate both their own and other people's emotions, which adversely affected the way they communicated with peers (Vasudevan, 2020). Since the service sector has grown to be the main driver of the nation's economic growth, pressure is particularly strong on personnel in this sector.…”
Section: Introductionmentioning
confidence: 99%
“…Research and publications on EI contribute to an increased awareness of the human dimension inherent in organizational dynamics and can guide practical actions within businesses and raise awareness among key stakeholders about its significance for organizational success. While a burgeoning body of literature on EI is evident across various domains, a recent review of the literature has brought to light a notable gap in the comprehension of EI, specifically within the banking sector (Vasudevan, 2020).…”
Section: Introductionmentioning
confidence: 99%